Glycogen synthase kinase is a regulator of the circadian clock of Neurospora crassa - Tataroglu, Ozgur; Lauinger, Linda; Sancar, Gencer; Brunner, Michael; Diernfellner, Axel (The journal of biological chemistry, 2012)
Timekeeping by circadian clocks relies upon precise adjustment of expression levels of clock proteins. Here we identify glycogen synthase kinase (GSK) as a novel and critical component of the circadian clock of Neurospora crassa that regulates the abundance of its core transcription factor white collar complex (WCC) on a post-transcriptional level. We show that GSK specifically binds and phosphorylates both subunits of the WCC. Reduced expression of GSK promotes an increased accumulation of WC-1, the limiting factor of the WCC, causing an acceleration of the circadian clock and a shorter free-running period.